(untitled) (E-BISNIS: JURNAL ILMIAH EKONOMI DAN BISNIS, 2025)
Tax arrears are one of the problems often faced by the government in its Tax arrears are a major obstacle to optimizing state revenue. As a major source of income, taxes play an important role in financing development and public services. This study analyzes the effect of tax audits, warning letters, enforcement letters, and tax seizure orders on tax arrears at the Pekanbaru Tax Office Tampan Tax Office for the period 2020–2024. The study uses a quantitative descriptive method with secondary data for 60 months and multiple linear regression analysis. The results of the study are expected to provide empirical evidence of the effectiveness of tax law enforcement in reducing arrears and to provide input for the tax authorities in formulating an optimal collection strategy